If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2u(u + 1) + 5(u + 1) = 0 Reorder the terms: 2u(1 + u) + 5(u + 1) = 0 (1 * 2u + u * 2u) + 5(u + 1) = 0 (2u + 2u2) + 5(u + 1) = 0 Reorder the terms: 2u + 2u2 + 5(1 + u) = 0 2u + 2u2 + (1 * 5 + u * 5) = 0 2u + 2u2 + (5 + 5u) = 0 Reorder the terms: 5 + 2u + 5u + 2u2 = 0 Combine like terms: 2u + 5u = 7u 5 + 7u + 2u2 = 0 Solving 5 + 7u + 2u2 = 0 Solving for variable 'u'. Factor a trinomial. (5 + 2u)(1 + u) = 0Subproblem 1
Set the factor '(5 + 2u)' equal to zero and attempt to solve: Simplifying 5 + 2u = 0 Solving 5 + 2u = 0 Move all terms containing u to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2u = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2u = 0 + -5 2u = 0 + -5 Combine like terms: 0 + -5 = -5 2u = -5 Divide each side by '2'. u = -2.5 Simplifying u = -2.5Subproblem 2
Set the factor '(1 + u)' equal to zero and attempt to solve: Simplifying 1 + u = 0 Solving 1 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + u = 0 + -1 Combine like terms: 1 + -1 = 0 0 + u = 0 + -1 u = 0 + -1 Combine like terms: 0 + -1 = -1 u = -1 Simplifying u = -1Solution
u = {-2.5, -1}
| (2z+9)(z+7)=0 | | j-87= | | 2250=(x+5)x | | bx+cy=b | | 5x-4=-5 | | v=4/3*3.14*8 | | 29+c= | | 5x+6=x+14 | | 5/8a+6 | | 4m^2+4mn+3mn+3n^2= | | -7x+1=x-55 | | 1/3(3w-15)=-1/5(25-5w) | | 11x+6=8x-6 | | 8+2m=-2-6m | | log(8)(x+2)-log(8)*x=2 | | 4x+4=6x+4 | | -2(2x+2)+3(x-4)= | | 12c=60 | | 38+7k=8(k*14) | | 6y^2-4y+3y-2= | | 2*x^2-12*x+10=0 | | y=3x^2+24x+44 | | 0=x(x+5)-2250 | | -2+3=6x-29 | | 2m+7=28 | | 24-(-24)=-48 | | x^2+4*x=21 | | 5x-(2x-5)=30 | | 8x^2+66x+70=0 | | 8x^2+66x+70=0 | | 5x-5=-6x+127 | | 4x+1=-x+26 |